Binge eating, but not dietary restraint, moderates the association between unhealthy food marketing exposure and sugary food consumption. (August 2020) - Egbert, Amy H.; Nicholson, Laura; Sroka, Anna; Silton, Rebecca; Bohnert, Amy M.
Abstract: Restrained eaters, those who exercise dietary restraint and often experience dietary lapses, may be particularly susceptible to food marketing. Findings are mixed as to whether restrained eaters consume more food after exposure to unhealthy food marketing, and little is known about whether food marketing may have more impact on those who exercise successful dietary restraint as compared with those who experience dietary lapses, such as binge eating. In the current study, participants were 38 young women, ages 18–22 years old. Both dietary restraint and binge eating were measured by the Eating Disorder Examination-Questionnaire. Participants viewed both unhealthy food commercials and non-food commercials two separate times in the laboratory, and ad libitum candy intake was subsequently measured. Results indicated that participants who endorsed binge eating ate significantly more candy than those who did not endorse binge eating after they viewed unhealthy food commercials F (1, 35) = 20.49, p  < .001, η2  = 0.37, but not after viewing non-food commercials. No significant differences in candy eaten emerged when comparing those who endorsed dietary restraint as compared to those who did not, regardless of commercial type. Findings demonstrate the importance of specific operational definitions of restrained eating to consider the differences between those who report binge eating, and those who do not. They also suggest that individuals who engage in binge eating may be particularly susceptible to overeating in response to unhealthy food marketing, marking a possible area for intervention. Highlights: Binge eating and dietary restraint are highly correlated. Binge eaters are receptive to unhealthy food marketing. Binge eating moderates the association between food marketing and candy intake.